Didactica de las ciencias para la educacion infantil - ADRIANA PATRICIA GALLEGO TORRES (Revista Científica, 2012)
This paper presents some perspectives on science education in the early grades of primary education. This is to make a round table on the impor- tance of how to approach science in the early ages responding to four questions What is a science education?, Educational Are science?, What are the factors of a historical, epistemological, didactic and pedagogical educational define that? and What is the educability that favors them? Answers are drawn from an overall perspective, then place them in pedagogical work, as noted, bring learners from primary to such natural sciences. It shall also examine issues that have to do with the curriculum and teacher training to the level specified. We have to clarify that this work is part of a series of works that are being developed in conjunc- tion with the Catholic University of Chile and the University of Peace in Barrancabermeja.